Analisis Kualitas Penggunaan Srikandi Sebagai Sistem Pengelolaan Tata Naskah Dinas Digital di Bappelitbangda Kota Cimahi - habbii hanizam, jihan; Achmad Sodik Sudrajat; Ono Taryono; Alika Novira (LPPM STISIP IMAM BONJOL, 2025)
This study examines the regional information system based on the implementation of Presidential Regulation Number 95 of 2018 concerning Electronic-Based Government Systems (SPBE). The use of the SRIKANDI application is regulated in ANRI Regulation Number 4 of 2021 concerning Guidelines for the Implementation of Integrated Dynamic Archival Information Systems. The objectives of this study are to: (1) Analyze the quality of SRIKANDI use in Bappelitbangda Cimahi City; (2) Identify obstacles in its use; and (3) Analyze the optimization strategies carried out by Bappelitbangda Cimahi City. The approach used is quantitative with data collection techniques through questionnaires, interviews, observation, and documentation. The research informants are Bappelitbangda employees who have used the SRIKANDI application. The theory used is the System Usability Scale (SUS) from John Brooke to assess the quality of system use. The results show that the quality of SRIKANDI use in Bappelitbangda Cimahi City is in the